Managing perturbations during handover meetings: a joint activity framework. Issue 3 (24th September 2015) - Mayor, Eric; Bangerter, Adrian
Abstract: Aim: To document the prevalence of perturbations of handover meetings and understand how nurses manage temporal, physical and social meeting boundaries in response to perturbations. Background: Handovers are joint activities performed collaboratively by participating nurses. Perturbations of handover are frequent and may potentially threaten continuity of care. Design: We observed and videotaped handovers during five successive days in four nursing care units in two Swiss hospitals in 2009. Methods: Videorecordings were transcribed. All perturbations during the handovers were noted. We performed content analysis of the sources of perturbations from the notes and interactional micro‐analyses of handover interactions based on video and transcripts. Results: Nurses are the most frequent sources of perturbations during handovers. Perturbations are collaboratively managed. A tacit division of labour is enacted via multimodal communication strategies, whereby perturbations are dealt with using both linguistic and bodily signals.